Nuclear power and the uranium market: Are reserves and resources sufficient? - Roman Mendelevitch; Thanh Thien Dang (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The increase of the use of atomic power in some emerging economies, in particular South Korea and China, has revitalized a discussion regarding the availability of uranium resources. Despite the fact that global uranium resources are more than sufficient to supply reactor-related demand for the rest of the century, some voices in the nuclear community expect a supply shortage for the upcoming decades, and the risk of prices tippling in the next 20 years. They argue with delayed construction times, untimely mining expansion and unfavorable market conditions. This Roundup takes a closer look at the arguments of the debate.
Keywords: 330